Studi Potensi Sampah dan Kandungan Residu Logam Berat pada Produk Sapi Potong yang Digembalakan di TPA Sampah “PUTRI CEMPO” Surakarta - Eka Handayanta (Universitas Sebelas Maret (UNS), 2008)
The aim of this research is to determine the potential of rubbish (quantity and quality) as cattle feeding and the heavy metal residues especialy Pb and Hg in beef cattle product (meat and viceral organ) wich is grazing in refusal place “Putri Cempo” Surakarta.The experiment have been carried out at refusal place “Putri Cempo” Surakarta where samples taken for quantity and quality of organic rubbish and beef catlle product for determine of heavy metal residues (Pb and Hg) especialy on meat (biceps femoris), liver, kidney and intestine. The result of this experiment indicated that organic rubbish at refusal place “Putri Cempo” Surakarta on DM basic, since 2002 – 2006 amount of 47,778 – 54,372 thousants ton/year. While nutrient content such as crude protein 10,00-12,79%, extract eter 4,05 – 7,94%, crude fiber 18,42 – 22,20%, and ash 21,73 – 24,33%, respectively. Heavy metal residues on meat, liver, kidney and intestine, Pb at amount of 2,16- 2,68 ppm which is up of the Indonesia National Standart, SNI (2,0 ppm), and Hg at amount of 0,01 -0,02 it is below of SNI (0,03 ppm).It could be concluded that higly potensitial of refusal place “Putri Cempo” Surakarta as catlle grazing. The other than, beef cattle product (meat) were not save for consumption.Key words : rubbish, refusal place, plumbum, merkury, cattle